Tourism Boom, Housing Doom: Excessive Tourism And International Emigration - Josip Mikulić; Vanja Vitezić; Stjepan Srhoj; Zvonimir Kuliš (Global Labor Organization (GLO), 2024)
Existing literature has largely overlooked the relationship between excessive tourism growth and international emigration. This study addresses this gap by analyzing Croatia, a country that experienced a significant population decline-losing 10% of its inhabitants between the 2011 and 2021 censuses-amid rapid and highly seasonal tourism growth. Coastal Croatia, in the later stage of the Tourism Area Life Cycle (TALC), contrasts with Continental Croatia, in its early stage. We first establish a positive association between rising housing prices and emigration across both regions. More critically, we demonstrate that tourism activity correlates with increased emigration in areas experiencing excessive tourism (late TALC stage), while it is negatively associated with emigration in regions with lower tourism levels (early TALC stage). Our findings shed light on the overlooked adverse effects of tourism growth in the later stages of the TALC, emphasizing the need for nuanced approaches to tourism development and public policy.
Keywords: O15; R21; R23; L83; 330; overtourism; housing prices; emigration; brain drain